CYP2C19 PHARMACOGENETIC TESTING FOR PERSONALIZATION OF ANTIPLATELET THERAPY IN PATIENTS WITH ACUTE CORONARY SYNDROME IN ROUTINE CLINICAL PRACTICE - A. I. Akhmetova; E. B. Kleimenova; D. A. Sychev; O. V. Parshina; L. P. Yashina (Столичная издательская компания, 2017)
Aim. To study the use of CYP2C19 pharmacogenetic testing (PhGT) for personalization of antiplatelet therapy in patients with acute coronary syndrome (ACS) in routine practice.Material and methods. The study included 103 patients with ACS without indications for long-term anticoagulant therapy, which underwent CYP2C19 PhGT aimed at antiplatelet therapy personalization.Results. According to CYP2C19 genotyping the GG, GA, AA allelic variants were detected. CYP2C19*2 PhGT revealed that genotypes GG, GA and AA were carried by 76 (73.8%), 23 (22.3%) and 4 (3.9%) patients, respectively. Initially 86 (83.5%) patients received clopidogrel, 17 (16.5%) - ticagrelor. After therapy correction based on genotype GA and AA, the proportion of ticagrelor receiving patients increased from 25.9% to 55.5% (relative risk=0.172; 95% confidence interval 0.075-0.396; p<0.001). In 40.7% of patients who were poor clopidogrel metabolizers increased clopidogrel doses during maintaining therapy can be associated with the increased risk of bleeding.Conclusion. PhGT results (detection of carriage of the CYP2C19*2 allele variant) was a significant predictor of antiplatelet therapy correction in ACS patients. Therapy personalization included the replacement of clopidogrel with ticagrelor or an increase in the clopidogrel maintenance dose to 150 mg per day, which did not affect significant clinical outcomes.